A New Parameterization of Coastal Drag to Simulate Landfast Ice in Deep Marginal Seas in the Arctic. Issue 6 (10th June 2022) - Liu, Yuqing; Losch, Martin; Hutter, Nils; Mu, Longjiang
Abstract: Landfast ice is nearly immobile sea ice attached to the coast. Landfast ice inhibits atmosphere‐ocean fluxes of heat, moisture, and momentum, leads to offshore flaw polynyas, and stores fresh river water in wintertime. Despite these important roles in coastal environments, landfast ice is not well simulated in current sea ice models, because landfast ice dynamics differ from the pack ice in the interior Arctic and require explicit parameterization. The dynamical mechanisms for landfast ice formation are linked to the local geography. Grounded ice ridges act as anchor points in shallow water. Coastlines and offshore island chains may also be pinning points between which arches of landfast ice can form in deep water. The grounding mechanism for landfast ice in shallow marginal seas has been successfully parameterized using bathymetry information, but this grounding scheme fails in deep regions. We describe a new landfast ice parameterization that uses lateral drag as a function of sea ice thickness, drift velocity, and local coastline length. The simulated landfast ice in a 36 km pan‐Arctic sea ice‐ocean simulation is compared to observations from satellite data and the effect of the new lateral drag parameterization is evaluated. The combination of the established grounding scheme for shallow water and the new lateral drag parameterization for deep water leads to an improved and realistic landfast ice distribution in most marginal seas in the Arctic. These results suggest that multiple mechanisms are at work to create and maintain landfast ice in marginal seas. Plain Language Summary: Landfast ice is sea ice that is attached to the coast and nearly stationary. In the Arctic, the stable landfast ice cover along the coasts of the marginal seas serves local communities for traveling and hunting, and provides habitat for Arctic wildlife. Two main processes lead to landfast ice: grounding of ice in shallow water, and anchoring to pinning points such as islands in the deep water. However, sea ice and ocean models to study the Arctic climate typically do not predict the distribution of landfast ice very well. Here, we present a new approach to representing the pinning effect of coastlines and islands. In our improved model, sea ice tends to stick to the coast and is more similar to observed landfast ice. We conclude that the new method will improve future projections of landfast ice in the Arctic that may prove useful for Arctic communities and wildlife management. Key Points: In a new landfast ice parameterization, static friction describes the lateral drag between sea ice and the coast The new parameterization improves landfast ice simulation in the Arctic, especially in the Kara Sea The results suggest that multiple mechanisms are at work to create and maintain landfast ice in marginal seas